ADOPTING SOCIO-DEMOGRAPHIC CHARACTERISTICS IN PROFILING GREEN CONSUMERS: A REVIEW OF HYPOTHESES - Arif Hartono (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
In the last three decades worldwide environmental consciousness has increased dramatically as well as profiling green consumers have gained tremendous attention in the past. Segmenting and targeting markets base on pro-environmental purchase behavior are essential when companies positioning their green products. Socio-demographic characteristics have gained a lot of attention as the key profiling variables. Such characteristics have been employed by many scholars more frequently for the bases of segmenting and profiling green consumers. However, most existing studies of green consumers’ socio-demographic were US based. The present article attempts to review the common hypotheses of socio-demographic characteristics in profiling green consumers. The present article reviews five general hypotheses relating to socio-demographics and environmental consciousness of green consumers, namely the gender, age, education level, income, and occupation hypotheses, as well as the theoretical explanation for each hypothesis. Most previous studies tend to have the same conclusion in the gender, age, education level, and income characteristics. Critics to socio-demographic characteristics and a need to conduct green marketing research in Indonesia was also reviewed.Key words: profiling, socio-demographic, green consumer, hypotheses.